Home intravenous diuretic administration for heart failure management: A scoping review - Morgan B. Krauter; Katherine S. McGilton; Stuti S. Patel; Karen Harkness; Tracey J. F. Colella (PLoS ONE, 2025)
Background Heart failure (HF) significantly impacts healthcare systems due to high rates of hospital bed utilization and readmission rates. Chronic HF often leads to frequent hospitalizations due to recurrent exacerbations and a decline in patient health status. Intravenous (IV) diuretic administration is essential for treating worsening HF. Emerging strategies include home-based IV diuretic therapy administration; however, limited practical implementation guidance is available. This scoping review aims to summarize the literature on home IV diuretic administration for HF patients, focusing on the interventions’ characteristics, and facilitators and barriers to its implementation. Methods This review followed the scoping review framework proposed by Arksey and O’Malley and PRIMSA-ScR. A comprehensive search was conducted across six databases (CINAHL, the Cochrane Library, EMBASE, MEDLINE, PsychINFO and Scopus) and grey literature to identify English studies from inception to April 13, 2024. Two independent reviewers screened articles and resources for inclusion and data was extracted using a form created by the authors in Covidence. Results The search yielded 2,049 results, with nine studies meeting the inclusion criteria. Studies varied in design, including feasibility, pilot, observational, and pre/post-intervention evaluations. The majority were conducted in European countries, with sample sizes ranging from 12 to 96 patients receiving home IV diuretics for HF. Key implementation challenges include appropriate patient selection, IV cannulation competency of healthcare providers, and multi-disciplinary and multi-agency collaboration. Conclusions Evidence on home IV diuretic administration practices for HF management remains limited. However, this scoping review suggests that commonalities across studies could form the basis for developing standard protocols in outpatient settings. Despite the lack of formal evidence-based guidelines, the findings also suggest that tailored, community-specific approaches and safe infusion guidance documents could enhance the efficacy and scalability of home IV diuretic therapy. Future research should focus on refining these strategies and exploring diuretic escalation methods beyond traditional acute care administration to optimize patient outcomes.